International Commodity Arrangements - Tsou, Stanley S.; Black, John D. (Quarterly Journal of Economics, 1944)
Scope of the paper: agricultural products chiefly, 521. — Present stage of developments, 522. — Existing commodity agreements: wheat, 523; coffee, 527; beef, 528; sugar, 528; tea, 530; non-agricultural products, 530; cartels, 531. — Buffer stocks, 532. — Wider distribution of food, 534. — Production adjustment, 536. — Chronic surpluses, 538. — Price stabilization: direct control schemes, 540; costs, 542.— Price lifting: tendency, 543; supporting prices, 544; desirability, 546. — The immediate postwar outlook, 547.— Conditions of success, 549. — Overhead organization, 551.